The low-cost remote steering control using the dc motor with feedback position - Tanawat Chalardsakul; Viroch Sukontanakarn; Chotnarin Piriyasilpa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The research proposed the design and installation of the DC motor with a feedback position used to control the steering direction of a rice-planting machine here will be converted into driverless robots. The MATLAB/Simulink software is used to simulate and measure signal drive from the servo controller board to obtain results that can be used to drive BTS 7960 motor driver module for the DC motor with feedback position. The SkyDroid T10 is used to remote control of steering direction of rice-planting machines and the mechanism to drive all robots. The results of test results of the robot spraying chemicals in rice fields were excellent. The operator can remotely control the robot through the camera from the mobile phone. The chemicals can be sprayed quickly, and the chemicals are distributed evenly and evenly into the ground.